#### Simplify:

[7√3 / (√10 + √3)] – [2√5 / (√6 + √5)] – [3√2 / (√15 + 3√2)]

**Solution:**

Let us simplify individually,

[7√3 / (√10 + √3)]

Let us rationalize the denominator,

7√3 / (√10 + √3) = [7√3(√10 – √3)] / [(√10 + √3) (√10 – √3)]

= [7√3.√10 – 7√3.√3] / [(√10)^{2} – (√3)^{2}]

= [7√30 – 7.3] / [10 – 3]

= 7[√30 – 3] / 7

= √30 – 3

Now,

[2√5 / (√6 + √5)]

**Let us rationalize the denominator, we get**

2√5 / (√6 + √5) = [2√5 (√6 – √5)] / [(√6 + √5) (√6 – √5)]

= [2√5.√6 – 2√5.√5] / [(√6)^{2} – (√5)^{2}]

= [2√30 – 2.5] / [6 – 5]

= [2√30 – 10] / 1

= 2√30 – 10

Now,

[3√2 / (√15 + 3√2)]

**Let us rationalize the denominator, we get**

3√2 / (√15 + 3√2) = [3√2 (√15 – 3√2)] / [(√15 + 3√2) (√15 – 3√2)]

= [3√2.√15 – 3√2.3√2] / [(√15)^{2} – (3√2)^{2}]

= [3√30 – 9.2] / [15 – 9.2]

= [3√30 – 18] / [15 – 18]

= 3[√30 – 6] / [-3]

= [√30 – 6] / -1

= 6 – √30

**So, according to the question let us substitute the obtained values,**

[7√3 / (√10 + √3)] – [2√5 / (√6 + √5)] – [3√2 / (√15 + 3√2)]

= (√30 – 3) – (2√30 – 10) – (6 – √30)

= √30 – 3 – 2√30 + 10 – 6 + √30

= 2√30 – 2√30 – 3 + 10 – 6

= 1

**More Solution:**

- Find the value of x2 + 5xy + y2.
- Choose the correct statement:
- Between two rational numbers:
- The product of any two irrational numbers is:
- Which of the following is an irrational number?
- The following is an irrational number?
- A rational number between √2 and √3 is:
- The decimal expansion of the rational number:
- 2√3 + √3 is equal to: